Determination of eight isoflavones in Radix Puerariae by capillary zone electrophoresis with an ionic liquid as an additive. Issue 3 (19th December 2014) - Xiao, Wen; Wang, Feng-Qin; Li, Chun-Hong; Zhang, Qian; Xia, Zhi-Ning; Yang, Feng-Qing
Abstract : A simple CZE method with ionic liquid as additive was developed for the simultaneous determination of eight isoflavones in Radix Puerariae. Ionic liquid shows potential applications as additive in CZE analysis of natural products. Abstract : Isoflavones are the main active components in Radix Puerariae, the dry root of Pueraria lobata or P. thomsonii . We developed a simple capillary zone electrophoresis (CZE) method with an ionic liquid (IL) as an additive for the simultaneous determination of eight isoflavones – ononin, daidzin, genistin, biochanin A, formononetin, puerarin, genistein and daizein – in Radix Puerariae. The experimental conditions, including the concentration of sodium tetraborate, the pH, the type and concentration of the ILs, the applied voltage and the capillary temperature, were investigated. The eight analytes (detection wavelength 260 nm) were well separated within 9 min using a running buffer of 30 mM sodium tetraborate and 50 mM 1-butyl-3-methylimidazolium tetrafluoroborate as an additive at pH 9.5, with an applied voltage of 18 kV and a capillary temperature of 25 °C. The method developed was fully validated (limit of detection, 1.72–4.92 μg mL −1 ; limit of quantification, 3.64–9.84 μg mL −1 ; intra-day precision, 1.1–4.7% RSD; inter-day precision, 2.1–6.6% RSD; and recovery, 93.1–107.5% with 4.0–5.9% RSD) and was successfully applied to the determination of the eight analytes in three Radix Puerariae samples. The results indicated that P. lobata contains more isoflavones than P. thomsonii . CZE with an IL as an additive is a promising method for the analysis of natural products.